Discovery of Kalmane Diterpenoids as Potent Analgesics from the Flowers of Rhododendron dauricum. Issue 9 (29th January 2022) - Feng, Yuanyuan; Zha, Suqin; Gao, Biao; Zhang, Hanqi; Jin, Pengfei; Zheng, Guijuan; Ma, Yilin; Yao, Guangmin
Comprehensive Summary: Kalmane diterpenoids, featuring a 5/8/5/5 tetracyclic carbon skeleton, are very rare in nature. The flowers of Rhododendron dauricum L. (Ericaceae) were phytochemically investigated for the first time, leading to the isolation of eight kalmane diterpenoids (1—8) including four new ones, named rhodokalmanols A—D (1—4). The structures of 1—8 were elucidated by comprehensive spectroscopic methods and 13 C NMR‐DP4+ analysis, and the absolute configurations of 1, 2, 4, and 5 were defined by single‐crystal X‐ray diffraction analysis with Cu Kα radiation. Rhodokalmanol A (1) represents the first 5, 8‐epoxykalmane diterpenoid and also the first kalm‐15(16)‐ene diterpenoid. Rhodokalmanols B—D (2—4) are the first examples of kalm‐7(8)‐ene, kalm‐16(17)‐ene, and 8 α ‐methoxykalmane diterpenoids, respectively. All the isolated kalmane diterpenoids 1—8 exhibited significant analgesic effects, and rhodokalmanol C (3) and kalmanol (8) expressed more potent analgesic activity than morphine at doses of 0.2 and 0.04 mg/kg. The preliminary structure‐activity relationships of kalmane diterpenoids as potent analgesics are discussed. Abstract : Eight kalmane diterpenoids (1—8) were isolated from the flowers of Rhododendron dauricum L. (Ericaceae). Rhodokalmanol A (1) represents the first 5, 8‐epoxykalmane diterpenoid and also the first kalm‐15(16)‐ene diterpenoid. Rhodokalmanols B—D (2—4) are the first examples of kalm‐7(8)‐ene, kalm‐16(17)‐ene, and 8 α ‐methoxykalmane diterpenoids, respectively. All the isolates exhibited significant analgesic effects. The preliminary structure−activity relationships are discussed.